Business Accounting 1 / Fifth Edition - Wood Frank (Pitman, 1989)
The most-widely used accountancy textbook in the world. Preface, The Accounting Equation and the Balance Sheet, The Double-Entry System for Assets and Liabilities, The Asset of Stock, The Double-Entry System for Expenses and Revenues, The Effect of Profit or Loss on Capital, Balancing Off Accounts, The Trial Balance, Trading and Profit and Loss Accounts: An Introduction, Balance Sheets, The Basic Structure of Accounting, The Banking System, Two Column Cash Books, Cash Discounts and the Tree Column Cash Book, The Sales Journal, The Journal, Valued Added Tax, Double Entry Records for Depreciation, Capital and Revenue Expenditure, Bank Reconciliation Statements, Suspense Accounts and Errors, Control Accounts, Manufacturing Accounts, Departmental Accounts, Columnar Day Books, Goodwill, The Valuation of Stock, Accounting Theory, Appendices, Index.